Preliminary Assessment of Genetic Diversity in the Earthworm Metaphire esupana (Thai & Huynh, 1993) from Southern Vietnam Based on COI Gene Sequences - Phan, Thanh Quốc; Lâm, Hải Đăng; Nguyễn, Đức Anh; Trần, Thanh Mến (Hue University Journal of Science: Natural Science, 2026)
This study provides a preliminary analysis of the genetic diversity of the earthworm Metaphire esupana (Thai & Huynh, 1993) in Southern Vietnam based on mitochondrial COI (cytochrome c oxidase subunit I) gene sequences. Ten representative specimens were collected from various locations, sequenced, and analyzed through phylogenetic reconstruction and MOTU delimitation. The analysis revealed four genetically distinct groups, with high bootstrap support values (mostly >90%), indicating significant genetic divergence. These groups may represent independently evolving lineages, potentially shaped by geographic isolation or local adaptation. The findings contribute to a deeper understanding of the genetic structure and diversification potential of Metaphire esupana (Thai & Huynh, 1993), and provide a valuable reference for taxonomy and biodiversity assessments of earthworms in Vietnam.